Autoimmunity-associated DIORA1 binds the MRCK family of serine/threonine kinases and controls cell motility - Tilen Tršelič; Nathalie Pelo; Gregoire Martin de Fremont; Vaishnavi S. Iyer; Elina Richardsdotter Andersson; Vijole Ottosson; David Alexander Frei; Elisa Baas; William A. Nyberg; Guðný Ella Thorlacius; Lara Mentlein; Sanjaykumar V. Boddul; et al. (Proceedings of the National Academy of Sciences, 2025)
Genetic association links disordered autoimmunity 1 (DIORA1) to numerous autoimmune rheumatic diseases, including systemic lupus erythematosus, Sjögren’s disease, rheumatoid arthritis, polymyositis, and systemic sclerosis. However, its cellular function has remained unknown. Here, we identify the Myotonic Dystrophy Kinase-Related Cdc42-Binding Kinases (MRCK kinases) family of serine/threonine kinases—key regulators of actomyosin contractility and cell motility—as direct interactors of DIORA1. Through interaction mapping, we show that DIORA1 binds three distinct modules of MRCK kinases, including the conserved kinase inhibitory motif, C1-PH, and citron homology domains. DIORA1 knockdown in human cells altered cellular phosphorylation patterns and reduced phosphorylation of known MRCK targets. RNA-sequencing and proteomic analyses revealed upregulation of epithelial–mesenchymal transition genes and proteins, and functional analyses confirmed increased cell invasion, following knockdown of DIORA1. Together, these findings identify the autoimmunity-associated DIORA1 protein as an interactor of MRCK kinases and a regulator of cell motility.